Natura e costrizione nel paragone della caverna - Ferrari, Franco (ΠΗΓΗ/FONS, 2017)
With the myth of the cave, Plato resumes one of the central motives of the Book 6 of the Republic, the dangers to which the philosophical nature is exposed, if its qualities are not accompanied by a proper educational pathway. With the liberation of the prisoners from the cave Plato represents the will to preserve the “natural philosopher” from the risks to which he is exposed by contact with the social and political dynamics of the sick city; only the educational constraint allows the liberation process to be entirely positive.